Analisis Laporan Keuangan Sebagai Alat Untuk Mengevaluasi Kondisi Finansial Pada Perusahaan (Dealer) Sepeda Motor Di Kota Pasir Pengaraian - Afriyanto - (Jurnal APTEK, 2009)
This research do to analize some Bicycle dealer company account report and to evaluate financial condition some bicycle dealer company in Pasir Pengaraian Town, is it good, not good or it worst. The method for this research is survey method that is tracing or observation. To analize financial report, use financial ratio that the result can measure and evaluate the work and the condition of company financial with more comprehensive include liquidate, solvablelity, profitablelity and activity.From the measurement report with the financial ratio, then the condition of UD. Prima Motor Pasir Pengaraian and CV. Surya Motor Jaya Pasir Pengaraian for ratio of liquidity, solvablelity and profitablelity, is in category good, but the financial both in category not good.